Phyllosticta species from banana (Musa sp.) in Chongqing and Guizhou Provinces, China - Wu, Shi-Ping; Liu, Yong-Xiang; Yuan, Jie; Wang, Yong; Hyde, Kevin D.; Liu, Zuo-Yi (Phytotaxa, 2014)
Six Phyllosticta strains were isolated from diseased leaves of Musa species in Chongqing and Guizhou provinces, China. Morphological and molecular analysis of LSU and combined ITS, ACT, TEF-1, and GPDH gene sequences, identified these strains as P. capitalensis (3 strains), P. musarum (1 strain) and two isolates were distinct from known Phyllosticta species. The latter is herein introduced as Phyllosticta musaechinensis sp. nov. A description and illustrations are provided, and the new species is compared with other species from Musa in this paper.